Ensiklopedia Tipografi Sebagai Media untuk Meningkatkan Pemahaman Terhadap Tipografi - Dian Rinjani; Maya Purnama Sari; Ayung Candra Padmasari (Jurnal Pendidikan Multimedia (Edsence), 2022)
Typography is one of the important elements in a multimedia product design. It is impossible to learn the science of typography from one course. Many terms exist in typography and can be learned by students to increase their knowledge of typography. One way to make it easier to know these typographic terms can be obtained from the encyclopedia. But the encyclopedia for typography does not yet exist. Based on this, the research is expected to be able to compile data on existing typographic terms which are then summarized into an interesting typographic encyclopedia and can improve student learning in multimedia education. After collecting data in the literature, it was continued to design a good typographic encyclopedia book and the next step was tested on 84 Multimedia Education students at the University of Pendidikan Indonesia who were contracting typography courses at the Multimedia Education Study Program, Universitas Pendidikan Indonesia. From the results of the trial, it was concluded that, through a good typographic encyclopedia book design, students could learn more easily about typographic terms.